In Vitro Amphotericin B Resistance in Clinical Isolates of Aspergillus terreus, with a Head-to-Head Comparison to Voriconazole - Sutton, Deanna A. (American Society for Microbiology, 1999)
Amphotericin B therapy continues to be the “gold standard” in the treatment of invasive aspergillosis in the immunocompromised host. Although Aspergillus fumigatus and Aspergillus flavus constitute the major species, several reports have described invasive pulmonary or disseminated disease due to the less common Aspergillus terreus and dismal clinical outcomes with high-dose amphotericin B. We therefore evaluated 101 clinical isolates of A. terreus for their susceptibility to amphotericin B and the investigational triazole voriconazole by using the National Committee for Clinical Laboratory Standards M27-A method modified for mould testing. Forty-eight-hour MICs indicated 98 and 0% resistance to amphotericin B and voriconazole, respectively. We conclude that A. terreus should be added to the list of etiologic agents refractory to conventional amphotericin B therapy and suggest the potential clinical utility of voriconazole in aspergillosis due to this species.